Motivational factors for professional staff: a case study of public libraries in Singapore. - Gwee, Hong Sung. (2008)
This study was carried out to identify and validate the factors of motivation for the professional staff in the local public libraries of National Library Board. This study also sought to identify the motivational factors perceived by the professional staff to be relevant and important in the context of NLB and finally to investigate the level of work motivation among the professional staff working in public libraries.